2018
DOI: 10.1177/0020872818804596
|View full text |Cite
|
Sign up to set email alerts
|

Life experience of pregnancy among Iranian homeless women

Abstract: This study aimed to analyse homeless women’s life experiences during pregnancy in shelters, drop-in centres and outreach services in Iran. In this qualitative study, thematic analysis was used to explore the experiences of 13 homeless women. The results showed that all participants were substance abusers, most commonly with methamphetamine. Consistent themes emerged from the data: (a) women’s understanding, feelings and actions regarding unplanned pregnancy, (b) violence in public places, (c) social rejection,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Though 78.4% of unhoused youth who used MA in the past week and only 60.5% of unhoused youth not using MA in the past week reported experiences of physical violence and physical altercations in the previous week, the difference between these groups approached, but did not meet statistical significance ( p =0.055; Martin et al., 2006). Two studies identified an association between MA use among women and being the victim of physical assault at the hands of non‐intimate partners (Lorvick et al., 2014; Sadeghi et al., 2021). In one of these studies, women who were unhoused and living in Iran reported that pregnancy was associated with an increased risk of experiencing physical victimisation by strangers in public places (Sadeghi et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Though 78.4% of unhoused youth who used MA in the past week and only 60.5% of unhoused youth not using MA in the past week reported experiences of physical violence and physical altercations in the previous week, the difference between these groups approached, but did not meet statistical significance ( p =0.055; Martin et al., 2006). Two studies identified an association between MA use among women and being the victim of physical assault at the hands of non‐intimate partners (Lorvick et al., 2014; Sadeghi et al., 2021). In one of these studies, women who were unhoused and living in Iran reported that pregnancy was associated with an increased risk of experiencing physical victimisation by strangers in public places (Sadeghi et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies identified an association between MA use among women and being the victim of physical assault at the hands of non‐intimate partners (Lorvick et al., 2014; Sadeghi et al., 2021). In one of these studies, women who were unhoused and living in Iran reported that pregnancy was associated with an increased risk of experiencing physical victimisation by strangers in public places (Sadeghi et al., 2021). Another study identified that individuals who were using MA were at risk of being victimised by law enforcement officers (Friedman et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations